Incidence, Risk Factors and Outcomes of Urinary Tract Infections among Patients Undergoing Thyroidectomy: Insights from the ACS-NSQIP - Usama Waqar; Warda Ahmed; Zoha Zahid Fazal; Ahmad Areeb Chaudhry; Haissan Iftikhar; Afsheen Ziauddin; Syed Akbar Abbas (International Archives of Otorhinolaryngology)
Introduction Urinary tract infections (UTIs) represent a rare postoperative complication following thyroidectomy.